The Effectiveness of Dia-Care Telemonitoring on Diabetes Outcome among Type 2 Diabetes Patients - Sukarno, Anita; Munthe, Evi Debora (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
Introduction: Social media is essential during Covid-19 outbreak to deliver tele-diabetes care continuously.Aim: This study investigated the effectivity of Dia-Care Telemonitoring using WhatsApp on diabetes outcomessuch as psychological distress, blood glucose level, and diabetes knowledge. Method: Randomized ControlTrial was conducted on type 2 diabetes patients in Kebon Jeruk and Kalideres Primary Care. In a 1-monthintervention, patients (n=72) were randomized to control and intervention group. All outcomes such as FastingBlood Glucose, Diabetes Knowledge Test, and Depression Anxiety Stress Scale were collected at baseline andafter 1-month intervention. Result: 30 patients completed the study (15 control group, 15 intervention group).Both control and intervention group significantly improved the diabetes knowledge and fasting blood after 1-month follow-up. Only intervention group significantly improved depression (mean= 2.47, SD= 1.59, p= 0.04).Conclusion: Dia-Care Telemonitoring using WhatsApp improved diabetes knowledge, fasting blood glucoseand depression level.